Peroneal spastic flatfoot in adolescents with accessory talar facet impingement: a preliminary report. Issue 4 (July 2015) - Niki, Hisateru; Aoki, Haruhito; Hirano, Takaaki; Akiyama, Yui; Fujiya, Hiroto
Abstract : This study analyzed imaging, arthroscopic findings, and treatment responses for peroneal spastic flatfoot (PSFF) caused by talocalcaneal impingement at the accessory anterolateral talar facet (AALTF) (accessory talar facet impingement) in 13 adolescents without histories of trauma and tarsal coalition. The AALTF was determined with computed tomography and MRI. Focal abutting bone marrow edema (FABME) on MRI around the AALTF was confirmed. In seven patients who underwent AALTF resection, subtalar arthroscopy was performed. All experienced alleviation PSFF after treatment; reduction in FABME was observed. AALTF resection alone is beneficial for PSFF caused by accessory talar facet impingement when peroneal spasms are restored by an injection of local anesthesia.